Association between gestational diabetes mellitus and risk of preeclampsia: a prospective observational case-control study in a tertiary care setting in Central India - Hiware, Sachin; Mahatme, Mohini S.; Kodape, Rahulkumar K.; Chati, Aarya A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Preeclampsia (PE) is a hypertensive disorder with significant maternal and fetal morbidity, often developing after 20 weeks of gestation. Gestational diabetes mellitus (GDM) is a common metabolic complication of pregnancy that shares pathophysiological mechanisms with PE, such as endothelial dysfunction and oxidative stress. This study aimed to assess the risk and correlation of preeclampsia in women diagnosed with GDM in a tertiary care setting in central India. Methods: A prospective, observational, case-control study was conducted over two months in the Department of Obstetrics and Gynecology. A total of 248 pregnant women were enrolled and categorized into two equal groups: GDM and control. Data were collected on glycemic profiles, blood pressure, and incidence of preeclampsia at baseline and after eight weeks. Statistical analysis included unpaired t-tests and Pearson correlation coefficients. Results: The incidence of preeclampsia was significantly higher in the GDM group (25.79%) compared to the control group (10.4%), with an odds ratio of 2.96 and a relative risk of 2.48. A positive correlation was observed between worsening glycemic parameters and the development of preeclampsia. The GDM group also required more pharmacological interventions, including insulin and antihypertensives. Conclusions: GDM significantly increases the risk of preeclampsia. Early screening, close monitoring, and tailored management of GDM are essential in mitigating maternal and fetal complications associated with hypertensive disorders in pregnancy.